ICT + PBL = Holistic Learning Solution: UTeM’s Experience - Shahbodin, Faaizah; Yusoff, Mariana; Che Ku Mohd, Che Ku Nuraini (2011)
This paper will highlight how ICT could be integrated in the whole processes of teaching and learning in Problem Based Learning (PBL) environment. The main focus in this paper is integrating of ICT components such as multimedia and internet technologies as a tool for PBL learning environment, and utilizing the problem based learning approach for the delivering instructions in the teaching and learning process at UTeM. This paper also share findings on the effectiveness of PBLAssess which been develop for this study. 56 respondents from the second year of study at UTeM who enrolled for the Human Computer Interaction course been selected for this study. Two research instruments were developed for the purpose of evaluating students’ performance and preferences which include, a set of questionnaires and prototype known as PBLAssess. Further Some of the current work on integrating ICT and PBL learning environment are shared. Understanding both the current state of the art for PBL and future prospects are the key issues in setting an agenda for future research and development in PBL.